Disappearing foot drop: a peroneal nerve ganglion - Hartman, Paul; LeGay, Douglas (DALHOUSIE MEDICAL JOURNAL, 2007)
A 38 year old man presented with extreme left leg pain. He had been unsuccessfully treated for many months before his condition resolved on its own. After some time his pain returned in a more severe form with swelling on the lateral aspect of the knee. MRI showed ganglion cyst compressing the common peroneal nerve, which was successfully removed and most function has been restored. This case is unique in the disappearance and reemergence of his condition, which is novel to the literature.